On the influence of molecular structure on the conductivity of electrolyte solutions - sodium nitrate in water - Krienke, H. (Condensed Matter Physics, 2013)
Theoretical calculations of the conductivity of sodium nitrate in water are presented and compared with experimental measurements. The method of direct correlation force in the framework of the interionic theory is used for the calculation of transport properties in connection with the associative mean spherical approximation (AMSA). The effective interactions between ions in solutions are derived with the help of Monte Carlo and Molecular Dynamics calculations on the Born-Oppenheimer level. This work is based on earlier theoretical and experimental studies of the structure of concentrated aqueous sodium nitrate solutions. Представлено теоретичнi обчислення провiдностi нiтрату натрiю у водi, порiвнянi з експериментальними вимiрюваннями. Метод прямої кореляцiйної сили в рамках мiжiонної теорiї використано для обчислення властивостей транспорту у зв’язку з асоцiативним середньосферичним наближенням (AMSA). Ефективнi взаємодiї мiж iонами в розчинах отриманi з обчислень методами Монте Карло i молекулярної динамiки на рiвнi Борна-Оппенгеймера. Ця робота базується на попереднiх теоретичних i експериментальних дослiженнях структури концентрованих водних розчинiв нiтрату натрiю.